Multilingual Lexical Development : A case of Children of Indonesian Immigrants in Taiwan - Madina madinas (English Language Teaching Prima Journal (ELT), 2020)
The number of immigrants increases tremendously in Taiwan. These recent immigrants originate from a variety of ethnicities; some are Han Chinese from Mainland China, others are mainly from Southeast Asian countries, with Vietnamese as the largest group, followed by Indonesians, Thai, and then Philippines. They brought with them their native languages and cultures (Chen,2010). Kuo (2008) found no difference in the lexical development of 2-6- year-old children of Vietnamese mothers and Taiwanese mothers, but children of Indonesian mothers were found to be slower (Kuo, 2015). This study aim to evaluate the the vocabulary size in Indonesian, Mandarin, and Taiwanese for children of Indonesian immigrants in Taiwan. The researcher investigated whether Indonesian mothers in Taiwan with limited Mandarin proficiency are able to provide the kind of input to facilitate their children’s Indonesian, Mandarin and Taiwanese acquisition or not.This study used Peabody Picture Vocabulary Test to assess their lexical development in Indonesian and Mandarin. The Taiwanese language measure tool is an application developed by Kuo (2017). This study revealed that the vocabulary score of Indonesian score were found to be lower than Mandarin and Taiwanese score and Mandarin score higher than Taiwanese score. The factors related to children’s lexical development were also investigated no correlation between Indonesian mother’s with their children in Indonesian language, because most of them communicate with their limited Mandarin or Taiwanese. Finally, this research should help people to have a better understanding about the phenomenon of multilingual family, where multilingual has become common in the society. Keyword : Multilingualism, lexical development, immigrant children, vocabulary size